Analisis Sistem Pengelolaan Dana Pensiun Syariah dan Dana Pensiun Konvensional - Muftihatus Sofiyah (Jurnal Ekonomi Manajemen Perbankan, 2022)
We can get a welfare guarantee for old age or retirement age through a pension fund. Therefore, the Pension Fund certainly requires good administration, so that it can be trusted and certainly useful for workers who will certainly have a retirement period later. There are 2 types of pension fund financial systems which, when viewed from a different management point of view, are sharia and conventional. The purpose of this study is to find out what is the difference between Islamic pension funds and conventional pension funds and how to manage them. The analytical method used in this research is a qualitative approach. With this method, the authors collect information by understanding journals and books and conduct in-depth research with the aim of obtaining the most appropriate data or information about how the management of Islamic pension funds and conventional pension funds differs. The management system in a sharia pension fund is: having an agreement (akad) in every transaction, having a sharia board, and when individuals are late in paying contributions, they are likely to be fined but the rewards of punitive support will be given to social funds. Meanwhile, ordinary conventional pension funds do not involve a contract when making transactions. And if individuals are late in paying dues, they will be penalized as interest.Keywords: Pension Fund, Sharia, Conventional